Examination of Students’ Academic Performance in Selected Mechanical Engineering Courses Prior-to-and-During COVID-19 Era - Olanrewaju M. Oyewola; Olusegun O. Ajide; Ibukun S. Osunbunmi; Yemisi V. Oyewola (Emerging Science Journal, 2022)
Advances in Information and Communications Technology (ICT) as well as the present challenges of COVID-19 have led to a new paradigm causing an absolute or partial transition from in-person classroom teaching-learning to online. There is little information available on research efforts that investigated the impact of an online learning approach on the academic performance of students in mechanical engineering-based courses. Therefore, the objective of this paper is the impact study of online learning mode as compared to in-person on academic performance of students in selected mechanical engineering courses in one of the Universities in South Pacific Islands prior-to-and-during COVID-19 Era. Data on grades obtained for 178 students that offered Fluid Mechanics, Thermodynamics, Heat Transfer, and Advanced Thermofluids (FTHA) courses were subjected to descriptive and non-parametric (Mann-Whitney and Kruskal-Wallis) statistical tests. Although descriptive analysis showed that online mode of instruction might influence a better academic performance in FTHA courses in comparison with in-person mode of instruction, the outcome of Mann-Whitney U and Kruskal-Wallis tests at specific p-values and corresponding z-values generally exhibited p-values higher than of 0.05, implying insignificant difference in performance between the two modes of learning investigated. Though the non-parametric statistical test results showed there was no significant difference in academic performance of students when online and in-person modes of learning were used, this, however, does not imply that a difference does not exist at all. Although the difference may be very trivial, descriptive analysis has shown that the online learning mode has at least exhibited better students’ academic performance when compared to in-person. It can be inferred from the foregoing that the online learning mode does not yield a negative response in respect of the performance of students who offered all four mechanical engineering courses. Based on the findings of this study, online is considered a reliable alternative to in-person or at least a suitable complement to in-person in the in-person-online hybrid mode during the ongoing COVID-19 era and other inevitable constraints in the future. Doi: 10.28991/esj-2022-SPER-017 Full Text: PDF